A new method for characterization of small capacity wind turbines with permanent magnet synchronous generator: An experimental study. Issue 8 (August 2018) - Verde, A.; Lastres, O.; Hernández, G.; Ibañez, G.; Verea, L.; Sebastian, P.J.
Abstract: This work presents a new and useful method to dimension wind turbines and control systems and to optimize their mechanical design. This method allows determining the principal curves for characterizing a small capacity wind turbine designed with a Permanent Magnet Synchronous Generator (PMSG). For the wind turbine characterization it was considered the losses in the process of energy transformation in the wind rotor, electric generator and in the bridge rectifier. The equivalent electric model of the synchronous generator was used to determine the electric parameter performance. The work of the wind rotor was considered in its maximum power curve and the PMSG performance in the linear region of its magnetization curve. This leads to develop a new methodology for the complete wind turbine characterization from the nominal parameters of the wind rotor and the electric generator. This method also allows obtaining the power curves and the parameters of voltage, current and efficiency around the wind speed domain and angular speed in the wind rotor. The method was tested for small-capacity wind turbine (1 kW and 10 kW) performances and the numerical and experimental results are described.